Solitary angiokeratoma of the tongue. - Farooq, U.; Mirzabeigi, M.; Vincek, V. (European Journal of Pediatric Dermatology, 2005)
Angiokeratoma refers to a rare group of lesions that have a characteristic dermal vascular dilatation, often associated with a number of metabolic disorders. Different forms of angiokeratoma have been described, which share the same histologic features but differ clinically. We report a case of an oral angiokeratoma in a 6 year old boy. This is to our knowledge the fifth case of oral angiokeratoma and the third pediatric case ever described.